Regulation of nuclear factor erythroid-2-related factor 2 as a potential therapeutic target in intracerebral hemorrhage - Zhang, Yuan; Yu, Wanpeng; Liu, Yingying; Chang, Wenguang; Wang, Man; Zhang, Lei (Frontiers in Molecular Neuroscience, 2022)
Hemorrhagic stroke can be categorized into several subtypes. The most common is intracerebral hemorrhage (ICH), which exhibits significant morbidity and mortality, affecting the lives of millions of people worldwide every year. Brain injury after ICH includes the primary injury that results from direct compression as well as stimulation by the hematoma and secondary brain injury (SBI) that is due to ischemia and hypoxia in the penumbra around the hematoma. A number of recent studies have analyzed the mechanisms producing the oxidative stress and inflammation that develop following hematoma formation and are associated with the ICH induced by the SBI as well as the resulting neurological dysfunction. Nuclear factor erythroid-2-related factor2 (Nrf2) is a critical component in mediating oxidative stress and anti-inflammatory response. We summarize the pathological mechanisms of ICH focusing on oxidative stress and the regulatory role of Nrf2, and review the mechanisms regulating Nrf2 at the transcriptional and post-transcriptional levels by influencing gene expression levels, protein stability, subcellular localization, and synergistic effects with other transcription factors. We further reviewing the efficacy of several Nrf2 activators in the treatment of ICH in experimental ICH models. Activation of Nrf2 might produce antioxidant, anti-inflammatory, and neuron-protection effects, which could potentially be a focus for developing future treatments and prevention of ICH.